2016
DOI: 10.1182/blood.v128.22.4684.4684
|View full text |Cite
|
Sign up to set email alerts
|

High Risk Multiple Myeloma: Better Outcomes with Upfront Tandem Autologous- Non-Myelo Ablative Allogeneic Stem Cell Transplantation Compared to Upfront Autologous Stem Cell Transplantation

Abstract: Aim/Background: The outcomes of high risk multiple myeloma (HR-MM) remain poor. As per the revised international staging system (R-ISS), high risk patients, defined by International Staging System (ISS) stage 3 plus high risk chromosomal abnormality and/or high Lactate Dehydrogenase (LDH), have particularly poor outcomes with 5 year progression free survival (PFS) and overall survival (OS) of 24% and 40% respectively.1 Tandem autologous - non-myeloablative allogeneic stem cell transplantation (ASCT-NMA AlloSCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They have been combined with the cytoreductive and immunosuppressive capability of ASCT, potentially improving outcomes in HR‐MM 3 . Several prospective trials have examined this ASCT‐NMA alloSCT approach compared to tandem ASCT with conflicting results 4–12 . A meta‐analysis combining six biological assignment trials with almost 1200 patients found no difference between the two approaches in either standard risk or HR‐MM 13 .…”
Section: Asct‐nma Allosct (N = 25) N (%) Asct‐alone (N = 17) N (%) P‐...mentioning
confidence: 99%
See 1 more Smart Citation
“…They have been combined with the cytoreductive and immunosuppressive capability of ASCT, potentially improving outcomes in HR‐MM 3 . Several prospective trials have examined this ASCT‐NMA alloSCT approach compared to tandem ASCT with conflicting results 4–12 . A meta‐analysis combining six biological assignment trials with almost 1200 patients found no difference between the two approaches in either standard risk or HR‐MM 13 .…”
Section: Asct‐nma Allosct (N = 25) N (%) Asct‐alone (N = 17) N (%) P‐...mentioning
confidence: 99%
“…3 Several prospective trials have examined this ASCT-NMA alloSCT approach compared to tandem ASCT with conflicting results. [4][5][6][7][8][9][10][11][12] A meta-analysis combining six biological assignment trials with almost 1200 patients found no difference between the two approaches in either standard risk or HR-MM. 13 Evaluation of outcome data from these trials is problematic; however, as they differ in study design with varying conditioning regimens and inconsistent definitions of HR-MM.…”
mentioning
confidence: 99%